ANALYSIS ANALYSIS OF THE INFLUENCE TRAINING AND WORK MOTIVATION ON PERFORMANCE IN THE HEALTH SERVICES OF EAST JAVA PROVINCE - Putri, Kirana Azahra; Swasti, Ika Korika (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
The purpose of this study was to explain the effect of training and work motivation on employee performance using research objects at Dinas Kesehatan Provinsi Jawa Timur. This research uses a quantitative approach. The population in this study were employees of the Health Office (Dinas Kesehatan) of Jawa Timur Province. The sample in this study was 72 respondents who had gone through calculations using the Slovin formula. The data analysis used in this research uses the component-based Structural Equation Modeling (SEM) method using the Partial Least Square (PLS) analysis tool. The results of this research show that training can have a positive and significant influence on employee performance, and work motivation has a positive and significant influence on employee performance.